Formulation and nutritional evaluation of galactagogue-based nutritional health mixes to support lactation - Durrani, Sanya; Hiremath, Netravathi; E., Shweatha H. (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Human breast milk is a rich source of essential nutrients and also contains protective elements such as antibodies and immune factors, along with hormones, growth factors, enzymes, and other bioactive compounds, which are designed for easy digestion and optimal absorption, ensuring the best possible growth and development of infants. However, dysgalactia or insufficient milk production, often linked to inadequate intake of calories and essential nutrients necessary for milk production, is a common hindrance to breastfeeding. In this context, the current study was planned to design and develop different variations of finger millet and oats-based galactagogue health mixes with the intent to encourage milk synthesis. Methods: Four galactagogue health mixes, namely GHM-R1, GHM-R2, GHM-O1 and GHM-O2 based on finger millet (25 and 50%) and oats (25 and 50%) with nuts and seeds, were developed. Foxnut flour-based health mix was used as a control. A descriptive sensory score card was used for sensory analysis. AOAC methods were used to analyse proximate and dietary fibre. Calcium and iron were analysed using standard protocols. Results: Among the developed galactagogue health mixes, the sensory quality of GHM-R1 (25% popped finger millet) was found to be highly acceptable with a score of 8.45. GHM-R2 (50% popped finger millet) reported the highest calcium content, 328 mg/100 gm. Conclusions: There lies great scope in scientifically evaluating the traditional knowledge systems based galactagogues for the mechanism, efficacy, dose, and safety.